2011
DOI: 10.1038/nn.2732
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal replay in the awake state: a potential substrate for memory consolidation and retrieval

Abstract: The hippocampus is required for the encoding, consolidation, and retrieval of event memories. While the neural mechanisms that underlie these processes are only partially understood, a series of recent papers point to awake memory replay as a potential contributor to both consolidation and retrieval. Replay is the sequential reactivation of hippocampal place cells that represent previously experienced behavioral trajectories and occurs frequently in the awake state, particularly during periods of relative immo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

62
835
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 823 publications
(899 citation statements)
references
References 80 publications
(139 reference statements)
62
835
1
1
Order By: Relevance
“…One possibility may be that theta and highgamma activity coordinate separate processes relevant for memory, such as attention or semantic processing, and that these processes occur separately in time during encoding and simultaneously during retrieval. However, another possibility is that the observed temporal compression complements previous studies suggesting that retrieval reactivates internal representations of an experience on a faster timescale than the original experience (33,34).…”
Section: Discussionsupporting
confidence: 70%
“…One possibility may be that theta and highgamma activity coordinate separate processes relevant for memory, such as attention or semantic processing, and that these processes occur separately in time during encoding and simultaneously during retrieval. However, another possibility is that the observed temporal compression complements previous studies suggesting that retrieval reactivates internal representations of an experience on a faster timescale than the original experience (33,34).…”
Section: Discussionsupporting
confidence: 70%
“…The relationship between the stimulus-induced and ongoing cortical activity revealed in our study has certain similarities with the "replay" of neuronal activity in neural circuits mediating episodic (9,24,43) and sensorimotor (44) learning. In those studies, the temporal firing patterns of multiple neurons during learning are repeated either during sleep (9,43,44) or in the awake state (25).…”
Section: Discussionsupporting
confidence: 54%
“…Indeed, sleep or anesthetized states are characterized by high synchronous activity due to widespread oscillations in the same frequency band and a global decrease in brain activity (23). Conversely, awake reactivation has been recently demonstrated during quiescent periods in hippocampal cells (24)(25)(26)(27)(28), and it has been shown to be influenced by the animal's current location (25)(26)(27)29), to occur with elevated precision in novel environments (25,29), and to represent pathways not previously experienced by the animal (28). Furthermore, a more recent study (22) found reactivation in awake rat visual cortical cells in response to a moving dot stimulus swept across a linear path of adjacent receptive fields following a conditioning period.…”
mentioning
confidence: 99%
“…Regions associated with episodic memory that are engaged during memory task performance have been observed to be active even during rest, reflecting ongoing reinstatement of episodic memories (Wilson & McNaughton, 1994;Carr et al, 2011;Jadhav et al, 2012). These memory reinstatements can lead to the incidental reinstatement of the context in which the memories were experienced (Bornstein & Norman, 2017).…”
Section: Ddm Resultsmentioning
confidence: 99%